Apoiando a construção de testes de aceitação automatizados a partir da especificação de requisitos - Silva, Carlos Breno Pereira (2012)
Automation has become increasingly necessary during the software test process due to the high cost and time associated with such activity. Some tools have been proposed to automate the execution of Acceptance Tests in Web applications. However, many of them have important limitations such as the strong dependence on the structure of the HTML pages and the need of manual valuing of the test cases. In this work, we present a language for specifying acceptance test scenarios for Web applications called IFL4TCG and a tool that allows the generation of test cases from these scenarios. The proposed language supports the criterion of Equivalence Classes Partition and the tool allows the generation of test cases that meet different combination strategies (i.e., Each-Choice, Base-Choice and All Combinations). In order to evaluate the effectiveness of the proposed solution, we used the language and the associated tool for designing and executing Acceptance Tests on a module of Sistema Unificado de Administração Pública (SUAP) of Instituto Federal Rio Grande do Norte (IFRN). Four Systems Analysts and one Computer Technician, which work as developers of the that system, participated in the evaluation. Preliminary results showed that IFL4TCG can actually help to detect defects in Web applications